1993
DOI: 10.1524/ract.1993.60.1.27
|View full text |Cite
|
Sign up to set email alerts
|

Radiochemical Investigation of the Behaviour of Lead in Groundwaters

Abstract: The behaviour of Pb at initial concentrations of 10" 7 mol/1 in three natural groundwaters is investigated as function of time using 210 Pb as tracer. The groundwaters are applied without filtration, after 0.45 μηι filtration and after 0.002 μιη ultrafiltration. The partition of Pb on the coarse particle fraction ( > 0.45 μηι), the fine particle (colloid) fraction (0.002 to 0.45 μηι) and the molecular fraction (<0.002 μηι) is determined. In most cases, the predominant amount of Pb is found with the coarse part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1993
1993
2005
2005

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 6 publications
(9 reference statements)
0
7
0
Order By: Relevance
“…The results of the investigation of the behaviour of Pb in natural groundwaters by use of 210 Pb have been reported in a previous communication [1]. In this paper the partition of Pb in groundwater/sediment systems, in particular the sorption of Pb and the influence of various parameters, the method of equilibration, the time of equilibration, the volume to mass ratio Vjm, the initial concentration of Pb and the pH are described.…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…The results of the investigation of the behaviour of Pb in natural groundwaters by use of 210 Pb have been reported in a previous communication [1]. In this paper the partition of Pb in groundwater/sediment systems, in particular the sorption of Pb and the influence of various parameters, the method of equilibration, the time of equilibration, the volume to mass ratio Vjm, the initial concentration of Pb and the pH are described.…”
Section: Introductionmentioning
confidence: 75%
“…humic and fulvic acids [1]. Therefore it can be concluded that these complexes are sorbed on the fine and coarse particles.…”
Section: System Gl/slmentioning
confidence: 96%
See 1 more Smart Citation
“…free ions, complexes, intrinsic colloids ("Eigenkolloide"), carrier colloids ("Fremdkolloide") and speciation of radionuclides has become an important branch of radiochemistry [3,57,[77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95],…”
Section: General Aspectsmentioning
confidence: 99%
“…[11]). This simple methodology, however, poses a number of methodological problems [12][13][14] and cannot be expected to give reliable results [3,15]. The diffusion technique [16] offers an attractive alternative because it allows to study sorption processes under experimental conditions held close to those in the environment.…”
Section: Introductionmentioning
confidence: 99%